2020
DOI: 10.1136/heartjnl-2020-316909
|View full text |Cite
|
Sign up to set email alerts
|

Do underlying cardiovascular diseases have any impact on hospitalised patients with COVID-19?

Abstract: ObjectivesAn outbreak of the highly contagious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has sickened thousands of people in China. The purpose of this study was to explore the early clinical characteristics of COVID-19 patients with cardiovascular disease (CVD).MethodsThis is a retrospective analysis of patients with COVID-19 from a single centre. All patients underwent real-time reverse transcription PCR for SARS-CoV-2 on admission. Demographic and clinical factors and laboratory data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
2
32
1
7
Order By: Relevance
“…Four studies were excluded due to unavailability of the full-text. Finally, 56 papers ( [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ) entered into meta-analysis for primary outcomes (mortality and ICU admission) and 198 papers [ 16 , 18 , [21] , [22] , [23] , [24] , [25] , [26] ,…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were excluded due to unavailability of the full-text. Finally, 56 papers ( [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ) entered into meta-analysis for primary outcomes (mortality and ICU admission) and 198 papers [ 16 , 18 , [21] , [22] , [23] , [24] , [25] , [26] ,…”
Section: Resultsmentioning
confidence: 99%
“…The clinical spectrum of COVID-19 appears to be wide, ranging from asymptomatic infection, mild to critically-ill cases (3)(4)(5)(6). Significant comorbidities such as type 2 diabetes mellitus (T2DM) and cardiovascular diseases (CVDs) were associated with developing severe and critical COVID-19 condition (7,8). In severe cases, patients can rapidly develop acute respiratory distress syndrome (ARDS), septic shock, and multiple organ dysfunction syndromes (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the Chinese population have reported that COVID-19 patients suffer from cardiovascular diseases, chronic respiratory diseases, and diabetes. [17][18][19] In Italy, COVID-19 patients with a concomitant cardiac disease had a poorer prognosis than those without cardiac involvement. 20 In contrast, several US studies have reported obesity as a recurrent clinical characteristic of COVID-19 inpatients, 16,21,22 which is likely because obesity is more prevalent in the US (~40%) than in other Western countries (e.g.…”
Section: Introductionmentioning
confidence: 99%